Preclinical characterization of an active immunotherapy targeting calcitonin gene-related peptide - Justin D. Boyd; Shixia Wang; Hsiao-Wen Lin; Yueh-Ting Hsieh; Yu Shuang Sun; Brett A. Thibodeaux; Hanxin Lu; Jaya Sahni; Jonathan Wiggins; Matthew S. Longo; Jeanne K. Brooks; Madeline M. Vroom; et al. (Communications Medicine)
Abstract Background The success of passive immunotherapies targeting Calcitonin gene-related peptide (CGRP) for managing migraine has prompted our efforts towards developing an active immunotherapy that induces the production of endogenous antibodies against CGRP. Achieving efficacious antibody titers via immunization could provide a more convenient and cost-effective treatment alternative to anti-CGRP monoclonal antibody (mAb) therapies. However, immunization against endogenous CGRP faces multiple challenges such as breaking immune tolerance, inducing sufficient antibody titers, and avoiding immune response-associated toxicity. Methods Synthetic peptide immunogens formulated in adjuvants were delivered intramuscularly. Serum samples were collected post immunization and used to measure antibody titers as well as for the isolation of antibodies specific to CGRP. Antibodies were characterized for their binding affinities and specificities. The capsaicin-induced increase in dermal blood flow model was used in rats for the assessment of the pharmacodynamic effect of immunization. Results Here we demonstrate that a peptide-based active immunotherapy designed to induce antibodies against CGRP promotes robust antibody titers across preclinical species. Characterization of the immune response strongly suggests that this peptide immunogen primarily stimulates a humoral response and only induced CGRP-specific antibodies. Antibodies produced by immunization are primarily IgG1 and demonstrate binding and activity potencies similar to marketed monoclonal antibodies against CGRP. Finally, immunization demonstrates in vivo efficacy in a rat pharmacodynamic model. Conclusion Our results strongly suggest that a peptide-based active immunotherapy against CGRP could provide an affordable and convenient therapeutic for the prevention of migraine.